PLACE, TIME AND BEING: A BRIEF REFLECTION ON THE HUMAN AGENDA IN POSTMODERNITY - da Silva, José Roberto Limas (Seven Editora, 2026)
This analysis reflects on the identity crisis of the contemporary subject in the face of transformations in the geographical categories of time and place. In this sense, the article aims to demonstrate the disconnections in the relationship between human beings and space and their social agenda, as well as the resulting anguish and anxiety. The research understands that the virtualization of time and space through the constant use of simultaneous technologies, such as the internet and social networks, has caused this chaotic social situation. The discussion presented in this article has already been the subject of bibliographic and documentary research, from a deductive perspective, in a paper presented at the International Congress of Advanced Studies in 2022. However, since it deals with a theme that directly engages with social experiences, the phenomenological method is present from the perspective of an existentialist hermeneutics of human facts and behaviors. The research points to an interesting path by analyzing the person of Jesus of Nazareth, considering him as an appropriate archetype for a behavioral shift in this anxious and distressed generation. Finally, the article advocates the need to recognize the transcendental dimension of the human being, reconciling essential nature with historical existence.DOI: https://doi.org/10.56238/sevened2026.001-033